PENGARUH TINGKAT BI RATE DAN GDP (GROSS DOMESTIC PRODUCT) TERHADAP KINERJA BISNIS DAN SOSIAL PERBANKAN SYARIAH DI INDONESIA DENGAN KONSEP RISK MANAJEMEN DAN KECUKUPAN MODAL SEBAGAI VARIABEL INTERVENING - Pratama, Angga Sukma (IQTISHODUNA, 2018)
The industry in Indonesia that survives the crisis in 2008 is sharia banking. In fact, the growth performance of Islamic banking financing remained high until February 2009 position with good performance. Therefore, the purpose of this study is to analyze the effect of BI Rate and Gross Domestic Product on Sharia Banking Performance in Indonesia. This research is descriptive research with quantitative method. The population in this study were Bank Indonesia, Central Bureau of Statistics, and Sharia Banking registered at Bank Indonesia in 2010-2015. For Syariah Banking, the sample is taken by purposive sampling. The type of data used in this study is secondary data. Data analysis used were: Normality test, Multicolinearity test of Heteroskedastity test, Linearity test, Autometeration test, Path Analysis, and t test. The results of this study illustrate that BI rate has indirectly affect the ZPR through NPF with a ttest of -2.07, and GDP indirectly affect the ZPR through CAR with a ttest of 17.569.